New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2) - Tan, Ming Kai; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2018)
Based on extended surveys in Kuala Belalong Field Studies Centre, Brunei Darussalam, one new species of Kuzicus is described here: Kuzicus mirabilis sp. nov. This represents the first species described from Borneo for this Asiatic genus. The female of Pulchroteratura huiqing Tan et al., 2017 is described here, first time for the genus. The females of Leptoteratura (Rhinoteratura) chela Tan et al., 2017 and Pseudoteratura (Pseudoteratura) kenuan Tan et al., 2017 are also described for the first time.